Epidemiological and Clinical Aspects of Primary Open Angle Glaucoma in Fianarantsoa Madagascar - Miray, L. G.; Rafanomezantsoa, R.; Rachid, A. L.; Andriamampionona, T. F.; Raobela, L. (Advances in Social Sciences Research Journal, 2024)
Introduction : Primary open-angle glaucoma (POAG) is a chronic, progressive, bilateral optic neuropathy corresponding to a loss of retinal ganglion cells and characterised by morphological changes in the optic disc associated with typical visual field damage. Methods : This was a prospective, cross-sectional, descriptive, monocentric study conducted over a 5-month period from September 2020 to February 2021 in the ophthalmology department of the university hospital of Tambohobe Fianarantsoa Madagascar. The purpose of this study was to evaluate the prevalence of primary open-angle glaucoma and to describe its epidemiological and clinical aspects. Results: The prevalence of primary open-angle glaucoma in our study was 21.25% with a female predominance of 68.63%. The mean age was 50 ± 15 years. The majority of patients (80.39% ) with POAG in our study had visual acuity greater than or equal to 20/63. 49 eyes or 48.94% of the 102 eyes had ocular hypertoni greater than 21 mm Hg. The Cup/Disc ratio greater than 0.5 was found in 99 eyes (97.06%). In our study, 61 of 102 eyes had a slightly altered visual field (59.80%), 30 eyes had a moderately altered visual field (29.41%) and 11 eyes had a severely altered visual field (10.78%). Conclusion : Primary open-angle glaucoma is a chronic progressive bilateral optic neuropathy corresponding to a loss of retinal ganglion cells and characterised by morphological changes in the optic disc associated with typical visual field damage. This pathalogy is very common in Fianarantsoa.